'Bacteroides mediterraneensis' sp. nov., a new human-associated bacterium isolated from ileum specimen. (September 2016) - Mailhe, M.; Ricaboni, D.; Vitton, V.; Fournier, P.-E.; Saber, K.; Raoult, D.
Abstract: We report here the main characteristics of ' Bacteroides mediterraneensis ' strain Marseille-P2644 T (CSURP2644) that was isolated from the stored samples of gut.